Molecular Identification of Baylisascaris transfuga from Gobiid Fishes: Parasite Prevalence and Fish Condition: Molecular Identification of Baylisascaris Transfuga from Gobiid Fishes (Sahel Journal of Life Sciences FUDMA, 2025)
Molecular biology methods are advocated for specific and accurate diagnosis of parasites. We examined gobiid fishes, Bostrychus africanus and Periophthalmus papilio, from four locations in Rivers State, Nigeria, for parasite identification using molecular biology techniques. Basket traps were used to capture the fish; gobiids were identified using specific guides, and meristic measurements were taken. Parasite isolation was done using standard procedures. The parasites were sorted based on morphological differences by wet microscopy, stored in absolute ethanol and transported to the Regional Centre for Biotechnology and Bioresources Research (RCBBR), University of Port Harcourt, for molecular identification. Two parasites were isolated: an acanthocephalan, which could not be sequenced due to an inadequate amount of DNA (